Meningkatkan Pengenalan Warna Melalui Finger Painting Pada Anak Usia 4-5 Tahun di PAUD Permata Bunda Muaro Jambi - Yesika Nadila (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2020)
This research is due to the undevelopment of color recognition in children seen from the time of the learning process. The purpose of this research is to improve color recognition through finger painting at the age of children 4-5 years. This type of research used class action research, with the research stage covering the preparation of the plan, implementation of action, observing and reflecting on the final outcome of the activities that have been implemented. This research focuses on children aged 4-5 years PAUD Permata Bunda Muaro Jambi which the subject of this study is a group of 15 children, consisting of 10 men and 5 women. Research is conducted in 2 cycles. Each cycle is 4 times the meeting. Data on research results are analyzed using quantitative descriptive analysis. Data analysis techniques are obtained through the filling of the orservation sheet of observations that form field records and documentation. The results showed that there was an increase in color recognition through finger painting activities in PAUD Permata Bunda Muaro Jambi, namely: from the preview only 20.67% of children know the color, The first Cycle 1st meeting  25.33%, first Cycle second meeting 35.33%, first Cycle in third meeting 46% and first Cycle 4th meeting 47.33%. In the second cycle the increase in color recognition of children already showed the first meeting 58%, the second cycle of the second meeting 68%, the second cycle of the 3rd meeting 80.67%, the end of second cycle of the 4th meeting  90% achieved the criteria of the value of the compensation is 90%. The 4th meeting reached 90%.